Role of Tourism Industry in the Developing of Economie to Iraq for (1990- 2009) - خضير ايمان عبد; كاظم عبير علي (Journal of Economics and Administrative Sciences, 2012)
The Developing economies of countries have witnessed essential changes to words the development of tourism industry in the 21st century . in addition to adopting same of policies and strategies to grow up with the tourism sector to make it one of the important economic sector to compete the tourist cal developments in the wear . As for the tourism sector in Iraq ,it’s still afresh one , has many of elements which can be in vested ,needs a wide strategies of tourist cal in statutes and variety completive services and change of success for the locale and forgin investor ,the essential aim after this research is to prompt the national economic through the tourism industry and making conciseness and recognizing of the official thirties in the country with importunes of this industry and necessary interest with this sector as a subsist to face frequency and reduce of the petroleum revenues that Iraq depends on which through the use same strategies in the planning and user from the experiences of same counters which go which have gotten wide steps in this respect